Licochalcone a Exhibits Leishmanicidal Activity in vitro and in Experimental Model of Leishmania (Leishmania) Infantum - Souza, Julia M.; de Carvalho, Érica A. A.; Candido, Ana Carolina B. B.; de Mendonça, Rafael P.; Fernanda da Silva, Maria; Parreira, Renato L. T.; Dias, Fernanda G. G.; Ambrósio, Sérgio R.; Arantes, Andrea T.; da Silva Filho, Ademar A.; Nascimento, Aline N.; Costa, Monique R.; et al. (Frontiers in Veterinary Science, 2020)
The efficacy of Licochalcone A (LicoA) and its two analogs were reported against Leishmania (Leishmania) amazonensis and Leishmania (Leishmania) infantum in vitro, and in experimental model of L. (L.) infantum in vivo. Initially, LicoA and its analogs were screened against promastigote forms of L. (L.) amazonensis. LicoA was the most active compound, with IC50 values of 20.26 µM and 3.88 µM at 24 h and 48 h, respectively. Against amastigote forms, the IC50 value of LicoA was 36.84 µM at 48 h. In the next step, the effectivity of LicoA was evaluated in vitro against promastigote and amastigote forms of L.(L.) infantum. Results demonstrated that LicoA exhibited leishmanicidal activity in vitro against promastigote forms with IC50 values of 41.10 µM and 12.47 µM at 24 h and 48 h, respectively; and against amastigote forms the IC50 value was 29.58 µM at 48 h. Assessment of cytotoxicity demonstrated that LicoA exhibited moderate mammalian cytotoxicity against peritoneal murine macrophages, the CC50 value was 123.21 µM at 48 h and showed about 30% of hemolytic activity at concentration of 400 µM. L.(L.) infantum-infected hamsters and treated with LicoA at 50 mg/kg for eight consecutive days was able to significantly reduce the parasite burden in both liver and spleen in 43.67% and 39.81%, respectively when compared with negative control group. These findings suggest that chalcone-type flavonoids can be a promising class of natural products to be considered in the search of new, safe and effective compounds capable to treat canine visceral leishmaniosis (CVL).